2013
DOI: 10.9790/3008-0711219
|View full text |Cite
|
Sign up to set email alerts
|

Potential Biodeteriogens of Indoor and Outdoor Surfaces (Coated With Gloss, Emulsion and Textcoat Paints)

Abstract: Potential Biodeteriogens of indoor and outdoor surfaces (coated with gloss, emulsion and text coat paints) within the University of Port Harcourt, Nigeria were investigated. Potential Biodeteriogens implicated in deterioration of painted surfaces were bacteria, fungi, microalgae and cyanobacteria. The total heterotrophic bacteria counts and total fungal counts for outdoor and indoor painted surfaces ranged from 2.8 x 10 6 to 9.00 x 10 6 cfu/g paint scrape, 1.56 x 10 4 to 6.6 x 10 4 cfu/g paint scrape; and 1.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, to date, different genera belonging to Pseudomonas, Micrococcus, Sphingomonas, Thiobacillus, Mycobacterium, Clostridium, Alcaligenes, Bacillus, Flavobacterium, Arthrobacter, Gallionella, and Shewanella have been characterized and reported in the literature as paint and painted surface-degrading strains (Gorbushina et al 2004;Ravikumar et al 2012). Concurrently, Bacillus species were also predominant among other bacterial species that have been most frequently isolated in several studies (Odokuma et al 2013).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…However, to date, different genera belonging to Pseudomonas, Micrococcus, Sphingomonas, Thiobacillus, Mycobacterium, Clostridium, Alcaligenes, Bacillus, Flavobacterium, Arthrobacter, Gallionella, and Shewanella have been characterized and reported in the literature as paint and painted surface-degrading strains (Gorbushina et al 2004;Ravikumar et al 2012). Concurrently, Bacillus species were also predominant among other bacterial species that have been most frequently isolated in several studies (Odokuma et al 2013).…”
Section: Resultsmentioning
confidence: 84%
“…In addition, the biodegradation efficiencies were significantly higher with glucose as an additional carbon source, in case of all the three Bacillus isolates. The potency of microbes as agents for degradation of several compounds thus indicates that biological treatment can be a promising alternative to attenuate environmental impact caused by pollutants (Bhattacharya et al 2012;Odokuma et al 2013). Similarly, Odokuma et al (2013) also reported that Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have shown that Bacillus sp exhibited the highest prevalence on painted surfaces, paintings, and paints. This may be attributed to the survival strategies evolved by it [33].…”
Section: Identification Of the Oil-based Paint Degradingmentioning
confidence: 99%